CROWN DOWN PREPARATION TECHNIQUE WITH LARGE TAPER ENDODONTIC HAND INSTRUMENT - Riany, Asri (Faculty of Dentistry, Mahasaraswati Denpasar University, 2021)
Introduction: Root canal preparation is an important step in root canal treatment. The use of stainless steel K-Files is time-consuming and causes fatigue to patients and operators. The large taper endodontic hand instrument can be used as an option for another preparation instrument. The purpose of this article is to determine the advantages of using large taper endodontic hand instruments as a preparation instrument compared to conventional stainless steel K-Files. Case: The 24-year-old male patient presented with pain in his lower left tooth even though it was not used. Examination of teeth 35, percussion and press (+), palpation (-), CE (-), exploration of root canals with smooth broach (+). There was a radiolucent image in the distal crown that had reached the pulp chamber, radiolucency with a blurred border of 2mm in diameter at the periapical area, and the dilation of the periodontal ligaments along with the roots. Tooth 35 diagnosis was partial pulp necrosiswith periapical lesions. Case Management: Root canal treatment of teeth 35 using hand-used ProTaper with the crown down technique up to F4 WL = 21mm. Obturation with single cone technique with Endomethasone as a sealer. Discussion: The large taper instrument is very flexible and easily enters narrow and bent root canals, thus it can shorten the working time, reduce the risk of fatigue for patients and operators, improves the cleaning of the root canal system, and consistent root canal formation. The crown down technique used can reduce the risk of preparation errors, prevent debris extrusion and improve obturation quality. Conclusion: Root canal preparation using a large taper endodontic hand instrument can shorten the working time and reduce the risk of fatigue for patients and operators compared to preparations using conventional stainless steel K-File.